2019
DOI: 10.3126/jcmc.v9i4.26899
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department length of stay and disposal of patients in Chitwan medical college, Nepal

Abstract: Background: Measuring patients Length of Stay (LOS) in the emergency Department (ED) is one of the assessments of quality indicators in terms of clinical, managerial and public satisfaction pro­spective. Waiting time standard is defined and its impact is analyzed in many hospitals especially in developed countries. Policy of emergency operations to reduce length of stay helps to manage overcrowding, spares time to treat critical patient and minimize preventable death. The study was done to assess length of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
1
Order By: Relevance
“…This duration was less than that from another tertiary care hospital from Nepal where the median length of stay was 3.84 hours while was 4.5 hours in another study. 14,15 Contrast to few studies where it was documented that 80% cases and 52% cases had length of stay <4 hrs, in our study it was 89.2%.…”
Section: Discussioncontrasting
confidence: 93%
“…This duration was less than that from another tertiary care hospital from Nepal where the median length of stay was 3.84 hours while was 4.5 hours in another study. 14,15 Contrast to few studies where it was documented that 80% cases and 52% cases had length of stay <4 hrs, in our study it was 89.2%.…”
Section: Discussioncontrasting
confidence: 93%
“…Previous studies conducted during pre-COVID-19 duration by Lamsal, et al showed a median of emergency length of stay as 3.84 hours with a minimum of 0.4 hours and maximum of 87.21 hours of stay. 11 In a study done by Chrusciel, et al the median LOS was 3.58 hours before the intervention and 3.10 hours after implementation of fast track in emergency department. 12 Likewise a study done by Hofer, et al the median length of emergency stay was found to be 2.06 hours.…”
Section: Discussionmentioning
confidence: 97%